Sensitivity analysis of the primary endpoint from the N-MOmentum study of inebilizumab in NMOSD. (November 2021) - Cree, Bruce AC; Bennett, Jeffrey L; Kim, Ho Jin; Weinshenker, Brian G; Pittock, Sean J; Wingerchuk, Dean; Fujihara, Kazuo; Paul, Friedemann; Cutter, Gary R; Marignier, Romain; Green, Ari J; Aktas, Orhan; et al.
Background: In the N-MOmentum trial, the risk of an adjudicated neuromyelitis optica spectrum disorder (NMOSD) attack was significantly reduced with inebilizumab compared with placebo. Objective: To demonstrate the robustness of this finding, using pre-specified sensitivity and subgroup analyses. Methods: N-MOmentum is a prospective, randomized, placebo-controlled, double-masked trial of inebilizumab, an anti-CD19 monoclonal B-cell-depleting antibody, in patients with NMOSD. Pre-planned and post hoc analyses were performed to evaluate the primary endpoint across a range of attack definitions and demographic groups, as well as key secondary endpoints. Results: In the N-MOmentum trial (ClinicalTrials.gov: NCT02200770), 174 participants received inebilizumab and 56 received placebo. Attack risk for inebilizumab versus placebo was consistently and significantly reduced, regardless of attack definition, type of attack, baseline disability, ethnicity, treatment history, or disease course (all with hazard ratios < 0.4 favoring inebilizumab, p < 0.05). Analyses of secondary endpoints showed similar trends. Conclusion: N-MOmentum demonstrated that inebilizumab provides a robust reduction in the risk of NMOSD attacks regardless of attack evaluation method, attack type, patient demographics, or previous therapy. The N-MOmentum study is registered at ClinicalTrials.gov: NCT2200770.